Psalm 63 : I thirst for you, oh God... : research article - Mare, Leonard P. (Ekklesiastikos Pharos, 2013)
The psalms should not only be the object of scholarly research, but also of devotional readings. Poetic texts have the innate ability to verbalize and articulate the journey of faith under various circumstances. Poetic imagination and the poetic word issue bold invitations to a new possibility of life and transformed faith. New vitality erupts from their daring summons to spiritual transformation. This transformative power of the poetic word places great authority and the ability to influence in the mouth of the poet. By their words, poets can create new realities and new beginnings. They are empowered through the dramatic artistry of the poetic word to bring about spiritual transformation in the hearts and lives of their hearers and readers. This article offers a reading of Psalm 63 that focuses on spiritual transformation. The yearning and thirst of the psalmist to encounter God speaks of the imaginative power of the poetic word to lead into spiritual transformation and renewal.
free